STUDI KUALITATIF PERAN IBU DALAM TOILET TRAINING PADA MASA PANDEMI COVID-19 DI POSYANDU ANGGREK DUSUN BONTITAN SENDANGAGUNG MINGGIR SLEMAN YOGYAKARTA - Retno, Andini; Pratama, Antonius Yogi (Jurnal Ilmu Keperawatan Komunitas, 2023)
Background:. Mothers play an important role in the success of toilet training for children, especially during Covid-19 pandemic. Phenomenon at the research site, there were some children aged 2-4 years old using diapers from morning to night and having a habit of defecating at any place. There were some parents who did not know about toilet training. Objective: This research aims to know the role of mothers in toilet training during Covid-19 pandemic at Posyandu Anggrek, Bontitan, Sendangagung Minggir, Sleman, Yogyakarta. Method: It was qualitative design with phenomenological approach. The population was 34 mothers. The sampling technique was purposive sampling with 6 participants. Data analysis used qualitative analysis. Result: The results revealed six main themes: 1) The role of mothers in minimizing the use of diapers. 2) How to do to toilet training. 3) Collaboration with other family members. 4) Observing children's readiness. 5) Motivator in toilet training. 6) Recognizing toilet training obstacle. Conclusion: The readiness of mothers and children as well as support by other family members can increase the success of toilet training, especially during Covid 19 pandemic. Suggestion: Further researchers are recommended to conduct research on relationship between mothers’ role and experiences in toilet training for children. Keywords: Toilet Training – Mother's Role xv + 70 pages + 2 tables + 2 schemas + 14 appendices Bibliography: 36, 2013 – 2021